Design and build a miniatured 3-axis translational stage - Muhammad Firdaus Kamarudin (Nanyang Technological University, 2020)
Microfluidics are also referred to as the attitude, management and manipulation of fluids that are constrained geometrically to small volumes. A microfluidic system typically handles transportation, mixing, separating, and processing of fluids. It involves different fields such as engineering, chemistry, physics, biochemistry, nanotechnology,and biotechnology. A microfabrication process was engaged to the magnetic polydimethylsiloxane membrane with micro-pillar arrays for the reduction of adhesion in residual droplets. An automated, accelerated and productive miniature device with a magnetic actuation would help in the processes of transportation, mixing, separating and processing of fluids. Microfluidic devices aim to precisely manipulate these small volumes of fluids.[1] However, there are manufacturers that specialises in microfluidic devices that could do most of the required processes, but it is quite costly for a device for one purpose. A multipurpose three-axis translational stage would also be too costly for this purpose.In this project, it aims to achieve the miniature device that helps to control the movement of the fluids for the process of transportation, mixing, separating,and processing. There were several prototypes in which were improved in the process of meeting the requirements of the project. The main key concept of the miniature device is to able to manipulate the movement and assisting the microfluidic processes that cost-saving and efficient. A miniatured three-axis translational stage will be used for these microfluidic processes. In this project, it aims to achieve the miniature device that helps to control the movement of the fluids for the process of transportation, mixing, separating, and processing. There were several prototypes in which were improved in the process of meeting the requirements of the project. The main key concept of the miniature device is to able to manipulate the movement and assisting the microfluidic processes that cost-saving and efficient. A miniatured three-axis translational stage will be used for these microfluidic processes.